Zakat accounting and public accountability: Evidence from Indonesia - Narulitasari, Devi; Mulya, Andwina Sekar Mawarni; Subagyo, Tamrin (JIFA (Journal of Islamic Finance and Accounting), 2023)
To what degree does muzakki enforce accountability on zakat institutions to verify the proper transmission of their zakat payments, as posited by the theory? The primary objective of this research is to examine the impact of zakat accounting, internal control, leadership, and organizational culture on public accountability within zakat institutions. The survey was carried out among managers of zakat institutions operating in the Yogyakarta and Surakarta regions. A purposive sampling technique was employed to determine the sample for this study. The research utilized the statistical method of Structural Equation Modeling (SEM) based on variance to analyze the collected data. The findings of the study indicate that zakat accounting, internal control, and organizational culture have a positive influence on public accountability, while leadership does not significantly affect public accountability in zakat institutions. The robustness testing conducted in this study further validates the significance of zakat accounting, internal control, and organizational culture as the primary predictors of public accountability. Theoretically, this research contributes by proposing a new construct, namely zakat accounting. The practical implications derived from this research underscore the importance of implementing zakat accounting practices within zakat institutions as a means to bolster public accountability.